2022
DOI: 10.5797/jnet.cr.2020-0164
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Acute Embolic Occlusion of the Common Carotid Artery in Which a Giant Thrombus Was Retrieved Using the Parallel Stent Retriever Technique

Abstract: We report a case of embolic occlusion of the common carotid artery (CCA) in which a giant thrombus was retrieved using the parallel stent retriever technique.Case presentation: An 84-year-old woman without anticoagulant therapy despite a history of cardioembolic stroke presented to our hospital because of left hemiparesis after developing sudden vision loss in her right eye. Emergency angiography revealed a giant thrombus in the right CCA. After arresting flow in the CCA using a balloon-guided catheter (BGC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…In endovascular procedures for patients such as the present case, blocking of the BGC by a giant clot during the procedure is often seen ( 2 - 7 ). We must remove the BGC and re-navigate the catheter to the target vessels to continue MT.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In endovascular procedures for patients such as the present case, blocking of the BGC by a giant clot during the procedure is often seen ( 2 - 7 ). We must remove the BGC and re-navigate the catheter to the target vessels to continue MT.…”
Section: Discussionmentioning
confidence: 85%
“…Our method, named the L-SHARE technique, might be effective for managing giant clots and have several advantages over previous reports (2)(3)(4)(5)(6)(7)(8)(9). First, the L-SHARE technique might facilitate repeated aspiration from the BGC through a long-sheath introducer, even if the BGC is obstructed by a clot and removed from the body.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have reported mechanical thrombectomy using aspiration through a balloon-guided catheter (BGC) 13 , 14) or an AC, 15) with a stent retriever under distal protection 11) or two parallel stent retrievers. 16) As mentioned above, aspiration with a BGC or an AC was ineffective in this case; therefore, a combined technique with a stent retriever was chosen. EmboTrap III 6.5 × 45 mm is a stent retriever with the largest diameter usable in Japan.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, even a sheath introducer (SI) may be occluded by a thrombus during MT. 2) This troublesome situation, as shown in Fig. 1 , occurs principally following withdrawal of the thrombus-occluded guiding catheter.…”
Section: Introductionmentioning
confidence: 99%